Relationship between Asset-backed Securities and Financial Performance of Listed Commercial Banks in Kenya - Ndungu, Stephen; Gichohi, Paul; Mutea, Fredrick (International Journal of Finance, 2020)
Purpose: The purpose of this study was to establish the relationship between asset-backed securities and financial performance of listed commercial banks in Kenya. Methodology: Descriptive survey research design was used. The target population was the listed commercial banks that are in Kenya. Census technique was applied in the study. Data was collected from 11 listed commercial banks in Kenya using closed-ended questionnaire. The required information was provided by all risk managers, finance managers, compliance managers and operations managers. To ensure validity and reliability, questionnaires were pre-tested with non-listed commercial banks in Kenya. The coded data was analyzed quantitatively where mean, percentage and standard deviation were computed while linear and multiple regression analysis were used to test the hypothesis, and information presented using Tables. Results: The findings showed that many banks either generally agreed with the statements on the questionnaires. The influence of asset-based securities on financial performance was at a mean 3.8227 and standard deviation of 1.38128. The adjusted R square value of 0.824 implied that asset backed securities predicted 82.4% of the variability in the financial performance. Therefore, asset backed securities could be used to predict financial performance. Unique contribution to theory, policy and practice: This study contributed the outcome of the relationship between asset-backed securities and financial performance of listed commercial banks in Kenya. Banks will be able to use securitization to free up with-held bank's capital in loans hence re-investing the capital in other ventures leading to improved financial performance. Commercial banks are recommended to issue more asset backed securities and there should be policies developed to guide commercial banks on asset backed securities This is because asset backed securities can partake in improving the capital structure of business banks in Kenya, thus, improving benefit and avoiding the base capital guideline edge.